1999
DOI: 10.1038/sj.gt.3300840
|View full text |Cite
|
Sign up to set email alerts
|

The extra- and intracellular barriers to lipid and adenovirus-mediated pulmonary gene transfer in native sheep airway epithelium

Abstract: Gene transfer to the respiratory epithelium is currently apical membrane represented a significant barrier to both suboptimal and may be helped by the identification of limitagents. Adenovirus-mediated expression could be signifiing biological barriers. We have, therefore, developed an cantly augmented by increasing contact time or by preex vivo model which retains many of the characteristics of treatment of tissues with a nominally calcium-free medium. in vivo native airways including mucociliary clearance,Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 36 publications
(38 reference statements)
5
89
0
2
Order By: Relevance
“…Concomitant downregulation of infection and inflammation may in itself improve transfection efficiency by decreasing some of the extracellular barriers to airway gene transfer. 16 A number of potential disadvantages of PLG microspheres also emerged from this study. Gene transfer efficiency, particularly in vivo, is likely too low for clinical efficacy, even though the vexed question of the level of gene expression needed to achieve clinical benefit in CF remains unresolved.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Concomitant downregulation of infection and inflammation may in itself improve transfection efficiency by decreasing some of the extracellular barriers to airway gene transfer. 16 A number of potential disadvantages of PLG microspheres also emerged from this study. Gene transfer efficiency, particularly in vivo, is likely too low for clinical efficacy, even though the vexed question of the level of gene expression needed to achieve clinical benefit in CF remains unresolved.…”
Section: Discussionmentioning
confidence: 96%
“…16 Transgene expression was assayed for up to 96 h and again compared with lipid-#67-mediated gene transfer. …”
Section: Duration and Efficiency Of Gene Transfer Ex Vivomentioning
confidence: 99%
See 2 more Smart Citations
“…NAC is a mucolytic agent, which exhibited an improved gene transfer in pulmonary epithelium for both viral and nonviral vectors. 25,26 Studies on the effect of mucus and the role of NAC in gene transfer of the gastrointestinal tract are limited. An earlier study showed that NAC removed the mucus between the villi, but no attempt of gene transfer was made.…”
Section: Discussionmentioning
confidence: 99%